Earthquake-Related Signals in Central Italy Detected by Hydrogeochemical and Satellite Techniques - Martinelli, Giovanni; Facca, Gianluca; Genzano, Nicola; Gherardi, Fabrizio; Lisi, Mariano; Pierotti, Lisa; Tramutoli, Valerio (Frontiers in Earth Science, 2020)
Central Apennines are one of the regions of highest seismic risk of Italy. A number of energetic events (M_W > 5) hit the region during the period 2004-2017, killing several hundreds of people (e.g., 294 casualties associated with the August 24th, 2016, M_W 6.0 event of Amatrice). These earthquakes impacted piezometric levels, springs discharge, and groundwater chemistry on a large area, even at distances of several tens of kilometers from the epicenters. Here we present a multidisciplinary dataset based on hydrogeochemical and satellite observations associated with the seismic events occurred in Central Italy during the period 2004-2017, that combines information derived from the application of groundwater monitoring and satellite techniques. Groundwater monitoring techniques allowed to detect hydrogeochemical anomalies in spring and well waters (20 sampling points over the observation period), whereas satellite techniques were applied to detect time-space variations in ground thermal emissions. We detected two significant, almost synchronous, anomalies in 2009 and 2016-2017 with both techniques, and we tentatively correlated them to crustal deformation processes. Part of the observed signals was detected before mainshocks, and they appear to be related to aseismic slip or to seismic slip eventually induced by minor fluctuations in seismicity. We argued that the combination of two factors, i.e., the shallow depth of local earthquakes and the concurrent deepening of groundwater circulation paths to several km depth, allowed for the recording of variations in the stress field by geofluids released at the surface.